2010
DOI: 10.1007/s13312-011-0061-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of prediabetes in school-going children

Abstract: Efforts must be made to recognize type 2 diabetes in the asymptomatic prediabetes state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 14 publications
(18 reference statements)
3
19
1
Order By: Relevance
“…Recent studies from India showed increasing prevalence of Type 2 diabetes in all regions like, 19.5% in Kerala (ADEPS), 15.5% in Chennai (CURES), 12.4% in Bangalore, 16.6% in Hyderabad, 11.7% in Kolkata and 9.3% in Mumbai (NUDS) [1]. In our study prevalence of IR was 16%.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Recent studies from India showed increasing prevalence of Type 2 diabetes in all regions like, 19.5% in Kerala (ADEPS), 15.5% in Chennai (CURES), 12.4% in Bangalore, 16.6% in Hyderabad, 11.7% in Kolkata and 9.3% in Mumbai (NUDS) [1]. In our study prevalence of IR was 16%.…”
Section: Discussionsupporting
confidence: 51%
“…Hence India is called the diabetic capital of the world contributing to nearly one fourth of world type II diabetes mellitus burden. An 80% of the cases are attributed to obesity, especially central abdominal obesity [1].…”
Section: Introductionmentioning
confidence: 99%
“…Majority of them were males i-e 80 (61.54%) and 50 (38.46%) were females. 115(88.46%) of the students having normal blood glucose level while the remaining PRE-DIABETES 1192 3 showed pre diabetes i-e 15(11.54%). Among them 11(8.46%) were males while 4(3.07%) were females.…”
Section: Resultsmentioning
confidence: 97%
“…2 Prediabetes contains impaired fasting glucose or impaired glucose tolerance and increases the risk factor for developing type 2 diabetes, micro vascular, and macro vascular diseases. 3 The old terminology of Border line had been replance by new term Impaired Glucose Tolerance in 1979 by World Health Organization and National Diabetes Data Group, in 1965, chemical or asymptomatic DM was coined. 4 In 1997, an expert committee from the American Diabetes Association (ADA) recommended the following criteria for PDM; a fasting blood glucose of 110 to <126mg/dl and/or a postprandial blood glucose of 140 to <200mg/ dl 2 hours after a 75 g oral glucose challenge.…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore evident that active management of pre-diabetes can be very effective in preventing the progression of diabetes. For modelling purposes the information given in Tables 3 (Narayanappa et al, 2011;Li, et al, 2009;NDS, 2011;Valensi et al, 2005) and 4 (Behl et al, 2004) was taken into account. Again the average data between men and women are presented.…”
Section: Fig 7 Prevalence Of Activitymentioning
confidence: 99%